Saluran dan Motif Gosip Mahasiswa Angkatan Daring - Widiastuti, Anindita (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2023)
Conditions for online batch university students have led to gossip being exchanged through different channels and with different motives compared to previous student batches that interacted face-to-face. Employing a phenomenological approach, data was collected through interviews to explore the gossip experiences of nine students who have exclusively attended online sessions since the beginning of their studies. The results revealed that LINE, WhatsApp, Instagram, and ZOOM were the channels used for gossip by the students. The research identified general motives, information validation motives, as well as social relationship motives for engaging in gossip. Understanding the channels and motives behind gossip will improve the quality of communication among students and with individuals in their circles. This research also aimed to provide insights into how information, particularly gossip, is treated in an intensive online situation.